Caries Management with the International Caries Detection and Assessment System II: Established Pit and Fissure Lesions - Jan Mitchell; Martha Brackett; William Brackett (Association of American Medical Colleges, 2017)
Introduction Operative dentistry addresses the surgical management of caries, a significant portion of dental practice. Dental students, who typically develop their skill sets in this important discipline by creating idealized preparations in plastic teeth, are often confused by the wide variety of tooth anatomy and caries presentation they see when they subsequently treat patients. To address this significant clinical transition issue, we developed this resource on preparing the moderate carious lesion using a stepwise, structured technique. Methods This resource consists of a flipped-classroom learning module and associated laboratory activity with an algorithm worksheet to practice critical thinking skills. Prior to the exercise, an interactive tutorial introduces the didactic background. The 4-hour class session starts with a short quiz and review, then learners use the worksheet to prepare and restore their tooth specimens. Results Learner response has been very positive. Moreover, faculty note that learners' skills in treating patients in clinic are noticeably higher and require less faculty intervention than was previously the case. Discussion Since new national curriculum standards for caries are currently being introduced, in addition to providing instruction to dental students, this resource presents an excellent opportunity to calibrate faculty members, who are a secondary learner group in this exercise, on a standard clinical protocol.